Hemorheologic Alterations in Patients with Type 2 Diabetes Mellitus Presented with an Acute Myocardial Infarction - Kyu-Hwan Park; Ung Kim; Kang-Un Choi; Jong-Ho Nam; Jung-Hee Lee; Chan-Hee Lee; Jang-Won Son; Jong-Seon Park; Dong-Gu Shin; Kyu-Chang Won; Jun Sung Moon; Yu Kyung Kim; et al. (Diabetes & Metabolism Journal, 2018)
BackgroundHemorheologic indices are known to be related to vascular complications in variable clinical settings. However, little is known about the associations between hemorheologic parameters and acute myocardial infarction (AMI) in type 2 diabetes mellitus (T2DM). The purpose of this study was to demonstrate the changes of hemorheologic environment inside of blood using hemorheologic parameters, especially the elongation index (EI) and critical shear stress (CSS) in diabetics with versus without AMI.MethodsA total of 195 patients with T2DM were enrolled. Patients were divided into the study group with AMI (AMI+, n=77) and control group (AMI−, n=118) who had no history of coronary artery disease. Hemorheologic parameters such as EI and CSS were measured and compared between the two groups.ResultsThe EI was lower (30.44%±1.77% in AMI+ and 31.47%±1.48% in AMI−, P<0.001) but the level of CSS was higher (316.13±108.20 mPa in AMI+ and 286.80±85.34 mPa in AMI−, P=0.040) in the AMI+. The CSS was significantly related to the erythrocyte sedimentation rate (R2=0.497, P<0.001) and use of dipeptidyl peptidase-4 inhibitors (R2=0.574, P=0.048).ConclusionDiabetics with AMI resulted in adverse hemorheologic changes with lower EI and higher CSS compared to diabetic subjects without AMI. Evaluation of the hemorheologic parameters may provide valuable supplementary information for managing patients with AMI and T2DM.